ANALYTICAL AND COMPARATIVE REVIEW OF THE LITERATURE ON THE RESEARCH TOPIC THE STUDY OF ADAPTIVE POTENTIAL AND PHYSICAL DEVELOPMENT IN THE BODY OF ORGANIZED YOUTH - Tajibayeva Dilafruz Rakhmonberdievna (Scholar Express Journals, 2023)
This article contains the history of the study of the formation of an objective method, the study of the adaptive capabilities of the body, which revealed the regular cyclicity of fluctuations in the work of the cardiovascular system, as well as the work of R. M. Baevsky, who in his numerous works was one of the first to describe the statistical analysis of HRV, introduced the basic concepts, summary vegetative indices, explained the regulation of the heart rhythm and the origin of individual HRV indicators. Anthropometric indicators of physical development, the main indicators of the circulatory system: heart rate, systolic blood pressure, diastolic blood pressure. The coefficient of health is used as a criterion for the adaptive capacity of the organism
Keywords: Adaptive potential; physical development of the body; heart rate variability